The combinations of selected parameters to prolong the network lifetime for cluster head selection in wireless sensor network - Din, W.I.S.W. (IEEE Computer Society, 2015)
In Wireless Sensor Network, parameter selection is one of the important considerations to help the usage of the energy while selecting the cluster head in clustering scheme. This paper proposed the right combination of the parameter to select the cluster head in order to minimize the total energy consumption required for data collection and aggregation. We proposed three parameters which are residual energy, centrality and communication cost and blended all together using Fuzzy Logic method. By using these proposed parameters, we will able to compare the energy usage for each of the nodes with LEACH and SEP algorithm. Simulation results show that, the right combination of parameters may produce good results and tends to prolong the lifetime of the sensor network. Â© 2014 IEEE.